ESTABLISHING THE CHILD'S RESIDENCE, TAKING INTO ACCOUNT THE CHILD'S BEST INTEREST - Bodea, Corina (International Journal of Legal and Social Order, 2024)
The Civil Code in force brought some changes in the matter of parental authority, the establishment of the child's residence and other measures that can be taken with regard to children, changes that brought to light a universally applicable rule: the principle of the best interest of the child. The transition from a divided parental authority to a parental authority exercised jointly and equally raised a series of problems. Both the legal subjects involved, mainly the parents, as well as the Courts constantly appealed to the best interest of the child, adopting different solutions from case to case